Can Term Limits Accelerate Women's Access to Top Political Positions? Quasi-Experimental Evidence from Italy - Carolina Kansikas; Manuel Bagues (Institute of Labor Economics (IZA), 2024)
We investigate whether term limits can help historically underrepresented groups, such as women, gain faster access to positions of political power. We exploit evidence from Italian local elections where, in a context of rapidly increasing women's presence in politics, mayoral term limits were extended from two to three five-year terms in municipalities with less than 3,000 inhabitants in 2014 and in those with a population between 3,000 and 5,000 in 2022. Using as control group slightly larger municipalities, we find that longer term limits delay younger cohorts' access to mayoral roles, significantly slowing the increase in female representation. The magnitude of the effect is substantial; the share of female mayors would be 4-10 percentage points higher if term limits had not been extended. The impact is stronger in municipalities with a larger presence of women at lower political levels and where gender quotas are in place, suggesting a complementarity between these policies. Our findings suggest that term limits help bridge the representational gap between entry and top-level political positions, especially in times of rapid societal change.
Keywords: J16; J18; J48; D72; 330; term limits; female political representation; Italian local elections